Desarrollo de una solución informática para la gestión de cartera de microempresarios. - Ramírez Bravo, Gianella Katherine (2021)
Nowadays, a large part of mobile applications help solve people's daily problems, facilitate communication, simplify tasks, optimize processes and improve quality of life. Accessibility to this type of technology is necessary every day to carry out activities such as: food, health, education, communication, work, and sports, among others. In particular, people who are microentrepreneurs often face the problem of portfolio management, that is, they manually perform the activities involved in the portfolio management process In effect, MANUAL portfolio management generates loss of information, ignorance of the status of the portfolio, delay in the development of activities, difficulty in handling and accessing information, due to which, there are economic losses. Therefore, the objective of the present Titling Work (TT) is to develop an IT solution for the management of micro entrepreneurs' portfolio, in order to provide a PROTOTYPE that allows the following activities to be carried out AUTOMATICALLY: client registration, credit or cash sales, payment method, product registration and reminders. In addition, to provide a control panel that helps microentrepreneurs to make optimal decisions. In this way, the mobile application developed provides an efficient solution to the problem raised above. Therefore, it contributes to the microenterprise process, provides competitive advantages, reduces economic costs (notebooks and pens) and is an environmentally friendly solution. On the other hand, in order to fulfill the general objective raised in the TT, a Systematic Literature Review was carried out, based on Barbara Kitchenham's methodology, which allowed the identification of the software solution (mobile application) and the technology (JavaScript programming language). Then, the Mobile-D methodology was used for the development of the mobile application, also, the Ionic Framework and the Firebase SDK platform were used as tools. Finally, the application was stabilized through an experiment with the participation of students belonging to the UNL-CIS obtaining a version 0.0.2, and was evaluated in a real environment, where it was concluded that the mobile application helped in the portfolio management of micro-entrepreneurs in 73%.